Pengaruh Pengaturan Keasaman Limbah Industri Teh Terhadap Pertumbuhan Miselium Jamur Tiram Cokelat (Pleurotus cystidiosus O.K. Miller) - Dalli Yullio Saputra; - Nurmiati; - Periadnadi (Jurnal Biologi Universitas Andalas, 2013)
The study about the effect of acidity adjusting of industrial waste of tea production on the mycelium growth of brown oyster mushroom (Pleurotus cystidiosus O.K. Miller) was conducted from January to April 2013 in the Laboratory of Microbiology, Department of Biology, Faculty of Mathematics and Natural Sciences, Andalas University, Padang. The aim of this study is to determine the effect of setting the acidity of tea production industrial waste and the mycelium growth of brown oyster mushroom. This research was designed by completely randomized design (CRD) with five treatments, which were pH 4, pH 5, pH 6, pH 7 and pH 8 in 5 replication. The results showed that the treatment of pH 8 and pH 7 on industrial waste of tea before weathering was optimum for the growth of mycellium (18 – 19,2 days) . Keywords: Acidity, waste of tea, Pleurotus cystidiosus, mycelium.